Sosok Etnis-Etnis Minoritas dalam Iklan (Figure of Minority Ethnic in Advertising) - Malau, Ruth (Universitas Semarang, 2011)
Differentiation between minorities and majorities will always be there in the middle of ethnic plurality in Indonesia, and the advertising was succesfully represented it within a spectacle s package in the form of culture s parody, in which figure of minority ethnics are used as an advertising s object to strengthen the colonial [obsession] that leads to the race dichotomy between black and white. Behind the images displayed by advertising, there are hidden minority myths that reveals the life of and the treatment received by minority ethnics in this country. The myths are ultimately based on ideologies of class, race, and language. Figure of minority ethnics, in advertising s package, describes the disorder of Indonesian s human diversity that caused by colonialism and those who inherited the Western civilization.